Integrating run‐time changes into system and software process enactment. Issue 9 (27th April 2016) - Tran, Hanh Nhi; Hajmoosaei, Mojtaba; Percebois, Christian; Front, Agnes; Roncancio, Claudia
Abstract: In System and Software Engineering development, unforeseen changes occurring during process enactment are almost inevitable but often poorly managed due to a lack of efficient mechanisms for spontaneously handling these run‐time changes. We proposed a change‐aware process management system that allows process actors reporting emergent changes, analyzing possible impacts, and notifying people affected by the changes. To this end, we integrated a Change Management Component with a Process Management System . The Process Management System monitors process enactment and uses the run‐time process information to construct a Process dependency graph ( PDG ) representing the dependencies among the elements of running processes. The Change Management Component captures change requests sent asynchronously, then reasons the PDG to determine impacted elements. Our PDG reflects the information of process instances and therefore can uncover the intra‐process or inter‐processes dependencies that are invisible on process models. We implemented a prototype named CAPE based on the platform jBPM and the graph database Neo4j. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Our change‐aware process management environment CAPE allows process actors dealing with emergent changes at run‐time. By creating a process dependency graph that provides a global view of all running processes and their dependencies, we can analyze possible impacts of a change and notify people affected by the change.